Pembuatan Pocket Hand Sanitizer Berbahan Dasar Daun Kersen (Muntingia calabura L.) Aroma Bunga Melati (Jasminum sambac) - Zainal Arifin; Nurul Afifah; Rizki Puspita Dewanti (Journal of Applied Agriculture, Health, and Technology, 2023)
A Folia Fresh is a hand sanitizer product in the form of a practical pocket spray made from natural base ingredients of Kersen leaf (Muntingia calabura L.) with a refreshing aroma of Jasmine Flower (Jasminum sambac). Kersen or talok (Muntingia calabura L.) is a kind of shade tree that we can easily find on the roadside. Kersen (Muntigia calabura L.) contains bioactive compounds, namely flavonoid, saponin, triterpene, steroid, and tannin which are compounds that have the potential as antibacterial. Cherry leaves extracts were obtained by maserasi using 70% ethanol as solvent. Cherry leaves were meserated for 21 x 24 hours to obtain the filtrate. The extract is then processed into a hand sanitizer product with the addition of aquadest, glycerin, methyl paraben, and the aroma of Jasmine Flowers. Jasmine flower has active substances that can help regenerate healthy skin, moisturize dry skin, and fight the symptoms of aging.